microRNA-93 promotes cell proliferation via targeting of PTEN in Osteosarcoma cells - Masanori Kawano; Kazuhiro Tanaka; Ichiro Itonaga; Shin‐ichi Ikeda; Tatsuya Iwasaki; Hiroshi Tsumura (2015)
Aberrant microRNA (miRNA) expression plays an essential role in osteosarcoma (OS) pathogenesis. Recent studies have shown that dysregulation of miRNA expression is associated with increased tumorigenesis and poor prognosis in several types of cancers, including OS. The aim of this study was to investigate the relevant microRNAs involved in the development of OS.To explore possible oncogenic factors in OS, we used a microarray-based approach to profile changes in the expression of miRNAs and their target mRNAs in five OS cell lines and human mesenchymal stem cells (hMSCs). An miRNA, miR-93, was significantly up-regulated, whereas phosphatase and tensin homologue (PTEN) expression was significantly down-regulated in all tested OS cells, when compared with hMSCs.When anti-miR-93 was transfected into OS cell lines, PTEN expression was greatly increased, suggesting that PTEN might be a target of miR-93 in ES cells. The expression of phosphorylated Akt protein, which is known to be inversely correlated with that of PTEN, was significantly down-regulated in anti-miR-93-transfected cells. Furthermore, transfection of anti-miR-93 inhibited the proliferation and cell cycle progression of ES cells. In addition, the down-regulation of miR-93 in these cells significantly suppressed tumor growth in vivo.Ectopic expression of miR-93 decreased PTEN protein levels. Furthermore, miR-93 increased proliferation and decreased apoptosis in OS cells, whereas its silencing in these cells inhibited such carcinogenic processes. Taking these observations together, miR-93 can be seen to play a critical role in carcinogenesis through suppression of PTEN, and may serve as a therapeutic target for the treatment of OS.